Impact of Neoadjuvant Bevacizumab on Neuroradiographic Response and Histological Findings Related to Tumor Stemness and the Hypoxic Tumor Microenvironment in Glioblastoma: Paired Comparison Between Newly Diagnosed and Recurrent Glioblastomas - Takei, Jun; Fukasawa, Nei; Tanaka, Toshihide; Yamamoto, Yohei; Tamura, Ryota; Sasaki, Hikaru; Akasaki, Yasuharu; Kamata, Yuko; Murahashi, Mutsunori; Shimoda, Masayuki; Murayama, Yuichi (Frontiers in Oncology, 2022)
Background: Previously we reported that bevacizumab (Bev) produces histological and neuroradiographic alterations including changes in tumor oxygenation, induction of an immunosupportive tumor microenvironment, and inhibition of stemness. To confirm how those effects vary during Bev therapy, paired samples from the same patients with newly diagnosed glioblastoma (GBM) who received preoperative neoadjuvant Bev (neoBev) were investigated with immunohistochemistry before and after recurrence. Methods: Eighteen samples from nine patients with newly diagnosed GBM who received preoperative neoBev followed by surgery and chemoradiotherapy, and then autopsy or salvage surgery after recurrence were investigated. Expression of carbonic anhydrase 9 (CA9), hypoxia inducible factor-1 alpha (HIF-1α), nestin, and Forkhead box M1 (FOXM1) was evaluated with immunohistochemistry. For comparison between neoBev and recurrent tumors, we divided the present cohort into two groups based on neuroradiographic response: Good and poor responders (GR and PR, respectively) to Bev were defined by the tumor regression rate on T1-weighted images with gadolinium enhancement (T1Gd) and fluid-attenuated inversion recovery images. Patterns of recurrence after Bev therapy were classified as cT1 flare-up and T2-diffuse/T2-circumscribed. Furthermore, we explored the possibility of utilizing FOXM1 as a biomarker of survival in this cohort. Results: A characteristic “pseudo-papillary”-like structure containing round-shaped tumor cells clustered adjacent to blood vessels surrounded by spindle-shaped tumor cells was seen in recurrent tumors. Tumor cells at the outer part of the “pseudo-papillary” structure were CA9+/HIF-1α+, whereas cells at the inner part of this structure were CA9−/HIF-1α+ and nestin+/FOXM1+. CA9 and HIF-1α expression was higher in T1Gd-PR and decreased in the “T2-circumscribed/T2-diffuse” pattern compared with the “T1 flare-up” pattern, suggesting that tumor oxygenation was frequently observed in T1Gd-GR in initial tumors and in the “T2-circumscribed/T2-diffuse” pattern in recurrent tumors. FOXM1 low-expression tumors tended to have a better prognosis than FOXM1 high-expression tumors. Conclusion: A “pseudo-papillary” structure was seen in recurrent GBM after anti-vascular endothelial growth factor therapy. Bev may contribute to tumor oxygenation, leading to inhibition of stemness and correlation with a neuroimaging response during Bev therapy. FOXM1 may play a role as a biomarker of survival during Bev therapy.